Seasonal variation of diarrheal diseases and drinking water quality in resettlement colony in Delhi, India: A community-based cross-sectional study - Risa Vernette Nengminza Sangma; S K Rasania; J G Prasuna; Ranjan Das; Manoj Jais (Indian Journal of Public Health, 2021)
Seasonal variation plays an important role in the occurrence of diarrheal diseases and distinct seasonal occurrence of diarrheal diseases, with bacterial diarrhea occurring more during the warm seasons and viral diarrhea occurring during the drier cool months, has been observed due to seasonal variation. Time-series cross-sectional study was conducted from January to December 2018 among 553 under-five children to assess seasonal variation of diarrheal diseases and its association with the drinking water quality in a resettlement colony of Delhi. The prevalence of diarrhea was 40.7% and was highest during the rainy season (67.6%). Majority of the water samples were found to be unsatisfactory for human consumption during the rainy and summer seasons. Significant and moderate relationship was found between the seasonal variation and occurrence of diarrhea (r = 0.728, P < 0.05) and most probable number count (r = 0.50, P < 0.05), respectively. Understanding the environmental factors that influences the occurrence of diarrheal diseases is warranted.